Potential and management strategy of floral biodiversity in the coastal areas in East Kalimantan, Indonesia - RUJEHAN RUJEHAN; PAULUS MATIUS (Society for Indonesian Biodiversity, 2018)
Rujehan, Matius P. 2018. Potential and management strategy of floral biodiversity in the coastal areas in East Kalimantan, Indonesia. Biodiversitas 19: 1130-1137. Some issues such as land clearing and mining activities often arise in the coastal areas of Bukit Soeharto Forest Park, East Kalimantan, Indonesia that serves as a water catchment area. The latest land cover in this area was dominated by bush or shrub and forest cover was reduced. This research was conducted in Tanah Merah Coast and around Samboja Reservoir in the coastal area of Bukit Soeharto Forest. The purposes of this study were to determine the potential diversity of flora in the two regions and to develop management strategies in order to maintain or even to improve the diversity of flora. The method used in this research was a survey using vegetation analysis and SWOT analysis. The results showed that the species of saplings and trees dominating the forest area of Tanah Merah Coast was Nauclea orientalis, while Cratoxylum arborescens was the most prominent species of seedlings. On the other side, the forest around Samboja Reservoir was dominated by Campnosperma auriculata for trees or adult communities, Ficus retusa for saplings and Dyera costulata for seedlings. Both species diversity (H') and evenness index (E) of these areas were categorized as medium. Management strategies needed to maintain and improve the diversity and evenness of existed flora consist of S-O strategy that aims to improve the ecological functions of the area that can provide economic benefits, S-T strategy proposes cooperation with local communities to develop alternative economic activities, W-O strategy utilize the funding opportunities from donor agencies for forest management and W-T strategy includes efforts to improve human resources through training in collaboration with donor agencies.